ENDOCRINOLOGY IN THE TIME OF COVID-19: Management of adrenal insufficiency. Issue 1 (July 2020) - Arlt, Wiebke; Baldeweg, Stephanie E; Pearce, Simon H S; Simpson, Helen L
Abstract : We provide guidance on prevention of adrenal crisis during the global COVID-19 crisis, a time with frequently restricted access to the usual level of healthcare. Patients with adrenal insufficiency are at an increased risk of infection, which may be complicated by developing an adrenal crisis; however, there is currently no evidence that adrenal insufficiency patients are more likely to develop a severe course of disease. We highlight the need for education (sick day rules, stringent social distancing rules), equipment (sufficient glucocorticoid supplies, steroid emergency self-injection kit) and empowerment (steroid emergency card, COVID-19 guidelines) to prevent adrenal crises. In patients with adrenal insufficiency developing an acute COVID-19 infection, which frequently presents with continuous high fever, we suggest oral stress dose cover with 20 mg hydrocortisone every 6 h. We also comment on suggested dosing for patients who usually take modified release hydrocortisone or prednisolone. In patients with adrenal insufficiency showing clinical deterioration during an acute COVID-19 infection, we advise immediate (self-)injection of 100 mg hydrocortisone intramuscularly, followed by continuous i.v. infusion of 200 mg hydrocortisone per 24 h, or until this can be established, and administration of 50 mg hydrocortisone every 6 h. We also advise on doses for infants and children.